Modeling the abundance of two Rhagoletis fly (Diptera: Tephritidae) pests in Washington State, U.S.A. - Wakie, Tewodros T. (PLoS One, 2019)
Well-adapted and abundant insect pests can negatively affect agricultural production. We modeled the abundance of two Rhagoletis fly (Diptera: Tephritidae) pests, apple maggot fly, Rhagoletis pomonella (Walsh), and western cherry fruit fly, Rhagoletis indifferens Curran, in Washington State (WA), U.S.A. using biologically relevant environmental variables. We tested the hypothesis that abundance of the two species is influenced by different environmental variables, based on the fact that these two species evolved in different environments, have different host plants, and that R. pomonella is an introduced pest in WA while R. indifferens is native. We collected data on fly and host plant abundance at 61 randomly selected sites across WA in 2015 and 2016. We obtained land-cover, climate, and elevation data from online sources and used these data to derive relevant landscape variables and modeled fly abundance using generalized linear models. For R. pomonella, relatively high winter mean minimum temperature, low elevation, and developed land-cover were the top variables positively related to fly abundance. In contrast, for R. indifferens, the top variables related to greater fly abundance were high Hargreaves climatic moisture and annual heat-moisture deficits (indication of drier habitats), high host plant abundance, and developed land-cover. Our results identify key environmental variables driving Rhagoletis fly abundance in WA and can be used for understanding adaptation of insects to non-native and native habitats and for assisting fly quarantine and management decisions.